2011
DOI: 10.1016/j.dld.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Changing aetiological factors of hepatocellular carcinoma and their potential impact on the effectiveness of surveillance

Abstract: a b s t r a c tBackground: The aetiological factors of hepatocellular carcinoma may vary over time. Aims: The study assessed the potential impact of the aetiological factors on the effectiveness of surveillance in real-world patients. Methods: Multicentre, cross-sectional study enrolling consecutive hepatocellular carcinoma cases during a six month period. Results: 1733 cases (1311 prevalent and 422 incident) were recruited (mean age 68.6 years; 46.1% cases over 70 years; 73.9% males; 95.3% with cirrhosis); 63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
(35 reference statements)
2
14
1
Order By: Relevance
“…In summary, since the first reports regarding the association of HCC with the newly discovered HCV the situation is dramatically changed in Italy, as well as in other western countries, where HCV was recognized as the most important aetiological factor. The most recent epidemiological data are beginning to depict a reduction in its relevance, as we recently reported also with respect to HBV and, overall, to viral infection‐related HCC and the patients’ mean age is getting substantially older, to confirm that, at least in Italy, HCV infection ‘tsunami’ is over and the disease is becoming a feature of elderly people. What used to be a disease characterized by a prognosis worse than in patients with other aetiologies is now a disease characterized by a median overall survival longer than 3 years because of a more careful patients surveillance, a consequent earlier diagnosis, with curative treatments being more frequently implemented.…”
Section: Discussionsupporting
confidence: 58%
“…In summary, since the first reports regarding the association of HCC with the newly discovered HCV the situation is dramatically changed in Italy, as well as in other western countries, where HCV was recognized as the most important aetiological factor. The most recent epidemiological data are beginning to depict a reduction in its relevance, as we recently reported also with respect to HBV and, overall, to viral infection‐related HCC and the patients’ mean age is getting substantially older, to confirm that, at least in Italy, HCV infection ‘tsunami’ is over and the disease is becoming a feature of elderly people. What used to be a disease characterized by a prognosis worse than in patients with other aetiologies is now a disease characterized by a median overall survival longer than 3 years because of a more careful patients surveillance, a consequent earlier diagnosis, with curative treatments being more frequently implemented.…”
Section: Discussionsupporting
confidence: 58%
“…With reference to the etiology, it is interesting to note that these results confirm the progressive decrease in the proportion of patients with HBVrelated HCCs among patients with liver cancer. In this series 8.8% of patients with active HBV infection was observed, and this percentage is even lower than that reported in Italy by Santi [Santi et al, 2012] and Stroffolini [Stroffolini et al, 2011] who observed a percentage of 10.6% and 13.3%, respectively. Differently, HCV infection remains the main etiological factor of HCC in Southern Italy with a percentage of 78.4%, representing more than two-thirds of cases observed, a figure higher than that observed in different Italian series in the last decade [Santi et al, 2012;Stroffolini et al, 2011;Cabibbo et al, 2012;Trinchet et al, 2007;Giovannucci et al, 2010;El-Serag et al, 2006].…”
Section: Discussioncontrasting
confidence: 69%
“…27 Interestingly, in all periods, viral patients were surveyed more frequently than non-viral cases (approximately 65% vs 38.5%), indicating that the aetiology influences the decision of implementing regular surveillance. 28 Indeed, although the efficacy of surveillance has been proven to be similar in viral and non-viral patients, 29 its effectiveness is lower in the latter group, as the condition of these patients is more rising number of non-cirrhotic HCCs (Fig. 2) Changes in both aetiology and diagnosis of HCC likely affected AFP levels at diagnosis.…”
Section: At-risk Patients Are More Surveyed Resulting In a Favourabmentioning
confidence: 99%
“…Interestingly, in all periods, viral patients were surveyed more frequently than non‐viral cases (approximately 65% vs 38.5%), indicating that the aetiology influences the decision of implementing regular surveillance . Indeed, although the efficacy of surveillance has been proven to be similar in viral and non‐viral patients, its effectiveness is lower in the latter group, as the condition of these patients is more influenced by “external” factors, such as: (i) a lower probability of being identified as carriers of liver disease; (ii) a lower probability of being under the care of gastroenterologists/hepatologists; (iii) a lower perception by care providers of HCC risk; (iv) a limited willingness and adherence to regular surveillance by alcoholic patients and (v) more frequent competing clinical concerns.…”
Section: Discussionmentioning
confidence: 99%